Religious Rituals Performed by Muslim Palliative Caregivers in Turkey During the Grieving Process: An Exploratory Study - Ümmühan, Aktürk (Journal of religion and health, 2022)
This study identifies the religious and cultural mourning rituals used by family members who provided care for palliative care patients. The study was conducted between January and February 2021. The research population was composed of family and community caregivers for patients in a palliative care unit at a hospital. The sample size was 245 people. An examination of the food rituals of caregivers during the mourning period showed that 47.3% thought it was appropriate to cook at the deceased patient’s residence for 7 days during the mourning period, 59.6% read Mawleed (prayer ritual) on the 3rd day after death and 56.3% offered halwa (food ritual) on the 3rd day. An examination of the religious rituals of the caregivers during the mourning period revealed that 97.6% prayed on the first day, 59.6% recited prayers for the lost one on the first ‘Eid after a death, and 83.3% read the Qur’an on the anniversary of the death. The study revealed that the majority of caregivers carried out religious and cultural rituals.